2013
DOI: 10.1007/s10803-013-2000-y
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Autistic Behaviors, Emotional and Behavioral Problems on Parenting Stress in Caregivers of Children with Autism

Abstract: This study examined the effects of autistic behaviors and individual emotional and behavioral problems on parenting stress in caregivers of children with autism. Caregivers were interviewed with the Childhood Autism Rating Scale and completed the Strength and Difficulties Questionnaire and the Parenting Stress Index Short Form. Results revealed that caregivers of children with mild/moderate autistic behavior problems perceived lower parenting stress than did those of children with no or severe problems. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 21 publications
9
54
0
4
Order By: Relevance
“…In relation to the second limitation, mothers with a history of clinical depression have been shown to report lower levels of prosocial skills for their children, than children themselves would report (Hay & Pawlby, 2003). Prosocial skill levels in our participants were indeed significantly lower than those of typically developing children, and thus similar to previous findings (Horiuchi et al, 2014;Huang et al, 2014;Iizuka et al, 2010;Russel et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In relation to the second limitation, mothers with a history of clinical depression have been shown to report lower levels of prosocial skills for their children, than children themselves would report (Hay & Pawlby, 2003). Prosocial skill levels in our participants were indeed significantly lower than those of typically developing children, and thus similar to previous findings (Horiuchi et al, 2014;Huang et al, 2014;Iizuka et al, 2010;Russel et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with evidence from two cross-sectional studies that have shown children's prosocial skills (assessed by the SDQ) to predict independently maternal parenting stress in families of children with an ID (Beck et al, 2004) and families of children with autism (Huang et al, 2014). Results from the present study extend these findings to indicate that these effects are longitudinal and include aspects of maternal psychological well-being not directly related to parenting (i.e., broader psychological distress and overall life satisfaction).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Individuals with ASD face daily challenges in multiple domains of their lives, including poor adaptive functioning, anxiety, hyperactivity, and obsessive-compulsive behaviors (Bauman 2010;Huang et al 2014;Peters-Scheffer et al 2012;Simonoff et al 2008;Wang et al 2011). Recently, studies have cited a rising trend in ASD prevalence worldwide, with increasing incidence of children with ASD in both Caucasian and Asian populations (Centers for Diseases Control and Prevention 2012; Elsabbagh et al 2012).…”
Section: Introductionmentioning
confidence: 99%